Effects of word length and word frequency among dyslexic, ADHD-I and typical readers - Norberto Pereira; Maria Armanda Costa; Manuela Guerreiro (Journal of Eye Movement Research)
This study aimed to investigate the neuropsycholinguistic functioning of children with Developmental Dyslexia (DD) and Attention-Deficit/Hyperactivity Disorder – inattentive subtype (ADHD-I) in a reading task. The psycholinguistic profile of both groups was assessed using a battery of neuropsychological and linguistic tests and compared to typical readers. Participants were submitted to a silent reading task with lexical manipulation of the text. Eye movements were recorded and compared aiming to find cognitive processes involved in reading that could help differentiate groups. The study examined whether word-frequency and word-length effects distinguish between groups. Participants included 19 typical readers, 21 children diagnosed with ADHD-I and 19 children with DD. All participants were attending 4th grade and had a mean age of 9.08 years. Children with DD and ADHD-I exhibited significant different cognitive and linguistic profiles on almost all measures evaluated when compared to typical readers. The effects of word length and word frequency interaction also differed significantly in the 3 experimental groups. The results support the multiple cognitive deficits theory. While the shared deficits support the evidence of a phonological disorder present in both conditions, the specific ones corroborate the hypothesis of an oculomotor dysfunction in DD and a visuo-spatial attention dysfunction in ADHD.